HEALTH EDUCATION AS A MEANS OF PREVENTING RISKY BEHAVIOR IN ADOLESCENTS - Yuniar Sari, Niken; Wahyuni, Sri; Cleodora, Cindy; Oktaviani Azhar, Nabila; Alif Ramadhan, Ichwanul; Mardinah, Shaffa; Minarni, Sri; Uyuni, Wardatul; Indri Saputri, Lutfiani; Nisa, Keisya Zahratun; Raja Gukguk, Christina; Waldain, Berry; Marito Siahaan, Alisia Oktaviani; Erikawati, Feby; Amin, Ismi (Jurnal Pengabdian Masyarakat Jurusan Keperawatan, 2025)
Risk behaviors among adolescents have become a serious concern in urban environments, including in Indonesia, due to their impact on physical and mental health as well as the future development of young generations. Several forms of risk behaviors commonly found among adolescents include premarital sexual activity, exposure to sexual-orientation–related social pressures, drug abuse (NAPZA), alcohol consumption, smoking, physical violence or fighting, bullying, and self-harm behaviors. A lack of knowledge and understanding regarding the dangers and consequences of such behaviors increases adolescents’ vulnerability to engaging in them. This community service activity aimed to improve adolescents’ knowledge, attitudes, and awareness in preventing and avoiding risk behaviors in RW 08, Sidomulyo Timur Village, Pekanbaru City. The method used was interactive lectures and group discussions using PowerPoint media, accompanied by pre-test and post-test evaluation involving 27 adolescent respondents selected through simple random sampling. The results showed a significant improvement in knowledge where, prior to the intervention, 16 respondents (59%) demonstrated low knowledge and 11 respondents (41%) demonstrated moderate knowledge. After the intervention, knowledge levels increased, with 24 respondents (89%) falling into the good category and 3 respondents (11%) in the moderate category. The 48% improvement indicates that health education is effective in enhancing adolescents’ understanding of risky behaviors and in promoting preventive efforts to support healthy growth and positive behavior among youth.